Estimation of Bladder pressure by using poiseuilles equation (Baghdad Science Journal, 2006)
Equation Boizil used to Oatae approximate value of bladder pressure for 25 healthy people compared with Amqas the Alrotinahh ways used an indirect the catheter Bashaddam and found this method is cheap and harmless and easy